The Reality of the Application of Online Learning Media at the Sukareja 02 State Elementary School During the Covid-19 Pandemic - Komaludin Komaludin (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The Covid-19 pandemic has had a major impact on the world of education in Indonesia. Educators must ensure that teaching and learning activities continue, even though students are at home. This research was motivated by the state of teaching and learning activities at SDN Sukareja 02 during the covid-19 pandemic. The application of online learning media for teachers and students is a must during covid. -19. The purpose of this study was to determine the problems of online learning in SD Negeri Sukareja 02, Brebes Regency. This type of research is descriptive qualitative. The data collection technique was done by interview. Data analysis used in this research is data collection, data reduction, data presentation and conclusions. The results showed that the reality of online learning at SD Negeri Sukareja 02 was not ready to be implemented because there were still obstacles including learning applications, internet networks and devices, learning management, e-mail, and assessment.